E-Learning using virtual reality for creating three Dimensional: Exploring the Potential of VR EdTech in E-Learning (Journal of Advances and Scholarly Researches in Allied Education, 2022)
Multiple decades of study have been devoted to examining the potential for and advantages ofimplementing VR into educational settings. It is possible to read about certain VR apps in the publishedliterature, but there is yet no comprehensive review of the market's offerings. In addition to tracking theevolution of VR edtech's offers, content, and features from 2019 to 2021, this research analyzes the marketfor VR edtech in that time period. Good educational policies that encourage students to apply whatthey've learned to real-world learning environments are crucial to students reaching their full potential.The goal of education should be to develop the whole person so that they may contribute in meaningfulways to the society of tomorrow. Knowledge alone is insufficient to meet the challenges of tomorrow'scivilizations, particularly in this age of fast change. Simply put, the information available today isinsufficient to address the challenges of tomorrow.